New media Audience: the change and competition - Shaykenova А.; Tleubay Т. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
The article provides an overview of changes in the readership, as well as modern technologies that have made great changes to the media industry in recent years. The competitiveness of classical (professional) journalism and other sources of information are also analyzed in order to draw the attention of the audience to themselves. In the literature published in different years in Russia («How new media changed journalism 2010-2016», A. Amzin and others, Yekaterinburg, Humanitarian University, 2016, «Audience of new media», Krishchanovich Polina, Pavlovskaya Carolina, 2016), it is talked about how the audience of new media has changed in the last 15-20 years, the interaction of technology and media is intensifying every day. And in foreign literature, specific differences are displayed in detail specific differences in the competitiveness of classical media and social media.